Faktor Determinan Kualitas Hidup Penderita Diabetes Mellitus - Mulyaningsih, M; Mursudarinah, M (Indonesian Journal on Medical Science, 2024)
Diabetes Mellitus (DM) is a type of non-communicable disease that is the number one cause of death in the world. The prevalence of DM is increasing from year to year. DM sufferers must carry out routine control so they can know the progress of the disease and the possibility of complications. Apart from that, routine control is also related to quality of life. However, it turns out that not all DM sufferers comply with treatment. This study aims to describe the determinants of quality of life for people with diabetes. This research is a descriptive study with a sample size of 61 DM sufferers. The results of the analysis show that from the physical component, the majority of respondents have good quality consisting of physical function (70.5%), physical limitations (55.7%), pain (88.5%), and general health (75.4%). Meanwhile, from the mental component, three aspects have good quality, and one aspect is poor. Mental components that have good quality consist of emotional limitations (59.0%), social function (55.7%), and vitality (57.4%), but for mental health, 57.4% of DM sufferers have poor quality. So, the conclusion of this study shows that the majority of DM sufferers have a good quality of life.